(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Reactive oxygen species (ROS) are founded in many health diseases and often generated from biological reactions or external factors. Natural antioxidant based on the prevention or treatment of complicated diseases has attracted an important deal of research interest. Phytochemical screening, total phenolic and flavonoid contents and hydrogen peroxide radical scavenging assays for evaluation of Salvadora persica (SP) in vitro antioxidant analysis of aqueous, methanolic and ethanolic extracts of roots were determined. It was found that the aqueous water gave the highest total extract yield followed by ethanol and methanol. Qualitative phytochemical screening showed the presence of different phytochemicals in water, methanol and ethanol extracts. Aqueous extract dispalayed the largest total phenolic contents followed by ethanolic and methanolic extracts while methanolic extract showed the higher flavonoids content than the ethanolic and aqueous extracts. Hydrogen peroxide scavenging method revealed that the aqueous and ethanolic extracts have good scavenging ability compared to gallic acid which used as positive control. there were strong negative significant correlations between hydrogen scavenging and phenolic contents (-0.369), but not with the contents of flavonoids. Also, the results revealed that there was a strong negative correlation between flavonoids and total phenolics. The results clearly indicate that root aqueous extract of Salvadora persica is having effective antioxidant activity.